Meaning of Unlawful and Unjust Termination of Employment in Labor Law: A Perspective from International Law and National Law - Achmad Jaka Mirdinata; Abdul Rachmad Budiono; Budi Santoso; Amelia Sri Kusuma Dewi (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2026)
This article examines the legal protection and justice for workers/laborers for unlawful termination of employment through a comparison between Indonesian labor law and international labor law standards. The main problem lies in the absence of an explicit normative definition of unlawful layoffs and the absence of a special compensation standard for workers/laborers who are terminated without valid reasons or without proper procedures. This study uses normative legal research methods with legislative, conceptual, case, and comparative approaches. The analysis focused on Indonesia's labor regulations, industrial relations dispute resolution mechanisms, the Government Regulation on layoffs, ILO Convention No. 158, the discourse on international labor rights, and court rulings related to unlawful layoffs. The results of the study show that Indonesian law has regulated layoff procedures and workers' rights, but has not explicitly distinguished between legal layoffs and unlawful layoffs as a separate legal category. In contrast, international labor law emphasizes the principles of legitimate cause, fair procedure, human dignity, and effective remedies as the standard of protection against unjust layoffs. This article argues that unlawful layoffs need to be constructed as a specific violation of a law that demands restorative justice, certainty of compensation, and access to effective dispute resolution.